ANALYSIS OF WATER DEMAND AND PLANNING OF MASTER PIPE IN PECATU VILLAGE, SOUTH KUTA SUBDISTRICT, BADUNG REGENCY - Ida Bagus Made Baskara Andika; Kristina Marta Nainggolan (Universitas Udayana, 2024)
Pecatu Village is one of the areas located in South Kuta, Badung Regency which is still experiencing an increase in drinking water demand due to the increasing population every year. The source of clean water needs in Pecatu Village is managed by Perumda Tirta Mangutama Badung Regency. The problem that occurs in Pecatu Village is the lack of clean water distribution to all residents who have subscribed or not subscribed to Perumda Tirta Mangutama. Therefore, it is necessary to analyze the need for drinking water and planning the size of the main pipe network in Pecatu Village. This research was conducted by projecting the population of Pecatu Village with a period of 10 years to 2033 using the Least Square method. The results of the analysis showed that the population of Pecatu Village in 2033 was 8839 people with a maximum day water demand is 22.10 L/s and water loss is 2,946 L/s. The main pipe planning is made into 4 segments which are placed based on the grouping of public roads based on their function with pipe diameters of 8 inch and 6 inch.